Excessive consumption of certain sea fishes and mushrooms may pose significant health risks - Seth, M; Mondal, P; Ghosh, D; Mukhopadhyay, SK (Bangladesh Journal of Scientific and Industrial Research, 2023)
Trimethylamine N-oxide (TMAO) is a diet-dependent molecule that causes atherosclerosis in human bodies. Elevated TMAO levels in the blood of type 2 diabetes and chronic renal disease patients have also been documented. This study examines trimethylamine (TMA) and TMAO levels in several edible mushrooms and marine fishes. According to the quantitative study, TMA and TMAO levels are high in the fish and mushroom samples. Although the examined marine fishes and mushrooms are considered nutritious and healthy, our data indicate that significant TMA/TMAO in those healthy foods may pose major health risks if ingested in excess. Bangladesh J. Sci. Ind. Res. 58(3), 187-190, 2023